PENGARUH PENGAWASAN, DISIPLIN KERJA, PENDIDIKAN DAN PELATIHAN TERHADAP PRESTASI KERJA - Rima Gustia Ningsih; Marzolina '; Sjahruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The aims of the research are to analyze the influence of control, labordiscipline, and education and training on customer service job performance. Population and sample 38 respondent. Data collecting is conducted by filling out some questionaire. Questionaire was structured in the from of likert scale. While the analysis tool use is descriptive analysis ang multiple linear regression analysis. There are two group of variable in this research. Those are independent variable which are control, labor discipline and education and training, and the other is dependent variable which is customer service job performance. This research result shown that partially variable of control, labor discipline and education and training have significant effect on performance, labor discipline is the most powerful variable affect job performance at PT. Telkomsel Shop Pekanbaru.Keywords: Control, Labor Discipline, Education and Training, Job Performance